Tradition chiite et islamisme khomeiniste (Note) - Durand, Edwige (Études internationales, 1994)
If we compare the religious tradition of Shi'ite Islam with the ideology Khomeini propounded from 1979 on, it emerges that Khomeini-style Islamism is more of a revolutionary political ideology falling within the category of Western Third-Worldism. It diverges from Shi'itism which has traditionally preached the illegitimacy of power, the need for contestation, the challenging of whatever is established, the search for social justice, the giving of support to the oppressed, and the expectation of a coming messiah. Khomeini exploited this tradition to serve political ends. He interpreted it in his own way and instituted a radical, infallible government of clerics while preaching anti-Westernism and Pan-Islamism intermixed with the exporting of his revolution. Shi'ite Islam has thus lost its traditional religious character, giving rise to confusion between religion and politics to the detriment of the former.